∂x∂u+∂y∂u=u.
Divide throughout by ∂x∂y, we get
"\\frac{\\partial u}{\\partial \\:y}+\\frac{\\partial u}{\\partial \\:x}= \\frac{\\partial{u}}{\\partial \\:x\\partial \\:y}"
Given u= "\\left(2x+a\\right)-\\sqrt{2y+b}"
Left side:
"\\frac{\\partial }{\\partial \\:x}\\left(\\left(2x+a\\right)-\\sqrt{2y+b}\\right)+\\frac{\\partial }{\\partial \\:y}\\left(\\left(2x+a\\right)-\\sqrt{2y+b}\\right)"
"\\frac{\\partial }{\\partial \\:x}\\left(\\left(2x+a\\right)-\\sqrt{2y+b}\\right)= 2"
"\\frac{\\partial }{\\partial \\:y}\\left(\\left(2x+a\\right)-\\sqrt{2y+b}\\right)= \\frac{1}{-\\sqrt{2y+b}}"
Hence left side is "2-\\frac{1}{\\sqrt{2y+b}}"
Right side:
"\\frac{\\partial }{\\partial \\:x\\partial \\:y}\\left(\\left(2x+a\\right)-\\sqrt{2y+b}\\right)" = "\\frac{\\partial }{\\partial \\:y}(2)" =0
Hence both sides are not equal and hence u is not the solution for given equation.
Comments
Leave a comment